1982
DOI: 10.1002/ar.1092030403
|View full text |Cite
|
Sign up to set email alerts
|

Association between mitochondria and rough endoplasmic reticulum in rat liver

Abstract: Mitochondria were isolated from rat liver homogenate by both zonal and sedimentation equilibrium centrifugation. From electron microscopic examination of thin sections it was observed that 81% of the isolated mitochondria were in contact with rough endoplasmic reticulum (RER). Intact, non-sectioned mitochondria subjected to negative staining procedures appeared to show points of connection between RER and the outer mitochondrial membrane. After treatment of mitochondria with digitonin to remove outer membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…As with caveolae, the SR may appear to engulf mitochondria, and thereby create a specialized space for Ca signaling, discussed below. Although close association between ER and mitochondria has been described in other cell types (489,561), few have reported the almost complete enveloping, which appears to be a feature of smooth muscles. This aspect has been examined in detail at the EM level by Dai et al (140) in pig tracheal muscle.…”
Section: E Sr and The Mitochondriamentioning
confidence: 90%
“…As with caveolae, the SR may appear to engulf mitochondria, and thereby create a specialized space for Ca signaling, discussed below. Although close association between ER and mitochondria has been described in other cell types (489,561), few have reported the almost complete enveloping, which appears to be a feature of smooth muscles. This aspect has been examined in detail at the EM level by Dai et al (140) in pig tracheal muscle.…”
Section: E Sr and The Mitochondriamentioning
confidence: 90%
“…Frequency It was initially suggested that 80% of mitochondria are in contact with ER in the liver (Montisano et al 1982). Later, more sophisticated analytical techniques revised downward this frequency and found that around 20% of mitochondria are in contact with ER at least in Hela cells (Rizzuto et al 1998).…”
Section: Important Structural Features To Take Into Account When Analmentioning
confidence: 99%
“…The specific role of Aux1p/Swa2p in regulating cortical ER inheritance was examined further by comparing the distribution of mitochondria and vacuoles in aux1/swa2⌬ and wild type. A close association between the ER and mitochondria has been described in both yeast and mammalian cells (Montisano et al 1982;Perkins et al, 1997;Prinz et al, 2000). To study the distribution of mitochondria in the aux1/swa2⌬ mutant, a plasmid (pYDY104) expressing a mitochondrial targeting sequence fused to RFP (Mozdy et al, 2000) was transformed into wild-type and mutant cells.…”
Section: Inheritance Of Other Organelles Appears To Be Unaffected In mentioning
confidence: 99%